(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
In the article, the authors investigate the issue of the use of wooden I-beams with steel tubular nodes in the designs of lamella roof. Wooden I-beams have been proven to be effective and now the are widely used in the construction of floors and coatings of simple shapes, however, the use in curved and polygonal structures is complicated due to the lack of developed nodes of their connections. In the article, the authors give a possible version of such a node, examine its stress-strain state in the work of a circular-mesh arch with a span of 12 meters. The aim of the work is to develop efficient and compact nodes of the wooden I-beams connection working as a part of lamella roof, to study the stress-strain state (SSS) of the developed node, the impact of its application on the SSS of structural elements and the bearing capacity of all the structure. The closest to the node presented in the article is the cross node, which is used in a lamella roof of the Paselnik system (without the use of steel elements). The cross node contains three jambs, which are combined, while two oncoming jambs enter on both sides with their spikes in the through jamb socket. The use of wooden I-beams as elements of the lamella roof will significantly facilitate their design, and the use of light nodes will simplify the process of their construction. The span of the structure under consideration is 18 meters, the height in the lock is 3 meters. The lamella roof consists of identical rectilinear jambs of the I-wooden beam, connected at right angles and whose length is 1515 mm. The considered lamella roof is assembled from wooden I-beams made of OSB with a wall of the following sizes: beam height 120 mm; belt height 40 mm; belt width 90 mm; OSB wall thickness 10 mm. The calculations in the "ANSYS WORKBENCH" and "LIRA-SAPR" software systems shows that the introduction into the calculation of the elements of the joints (steel pipes) significantly affects the stress-strain state of the all structure due to not only an increase in geometric characteristics and bearing capacity in nodes, but also, possibly, due to the work of these elements as stiffeners, which reduce the deformation of wooden I-beams and take on the action of torque, due to the fact that they are sections of a closed loop. Due to this work, the voltage in the connecting elements is more than 10 times higher than in the wooden I-beams, which is acceptable and, moreover, allows you to more fully use the capabilities of the material from which they are made - steel.